Analisis Faktor-Faktor Pasar dan Pengaruhnya Terhadap Return Saham pada Perusahaan Pertambangan Subsektor Batubara yang Terdaftar di Bursa Efek Indonesia - Rudianto, Dudi (Business and Management Review, 2011)
Coal is a commodity most important energy source, which is ready as a substitute for crude oil, which is increasingly scarce and expensive. Coal companies in Indonesia is growing rapidly and dominate the mining sector issuers in Indonesian Stock Exchange (IDX). Mining sector index was long enough to reach the highest values compared to other sectors in the IDX, and which became the main driving force is the issuer of coal. The purpose of this study was to determine the effect of changes market factors, which are the Price Earning Ratio (PER), market risk and the international crude oil prices as an independent variable on stock returns five largest issuers in the IDX coal as the dependent variable. Research is a causal study, some variables data sample selection was done by purposive sampling method. Period of data collection conducted over five quarters starting in Quarter-1 2009 until Quarter-1 2010. Results showed that all independent variables simultaneously influential to return the stock of coal, but only partially proven PER (market ratio) significantly affect to return the stock of coal. Based on multiple regression equation of changes in the PER and the international crude oil prices would  affect the return of the stock of coal in the IDX. Keywords: Return the stock, price earning ratio, systematic risk and crude oil price